Paciente femenino de 32 años de edad con hepatitis a y obesidad tipo 2 - Bajaña Hernández, María Matilde (2021)
The present clinical case deals with a 32 year old female patient, single, right-handed marital status, kindergarten teacher, presents a family pathological history such as hypertension and diabetes, but no personal pathological history. It is referred to the nutritionist because the signs and symptoms coincide with the pathological picture of Hepatitis, reflected in the biochemical evaluation, referring to liver tests, in which values are found outside the normal ranges, the same ones that confirm a medical diagnosis of Hepatitis A. It has a weight of 82kg and a height of 151cm, in which, by anthropometric assessment. it presents a Boy Mass Index(BMI) of 35.96kg/m2, which indicates that it is in a nutritional state with type II obesity, it is make dietary prescription, the same that same that will be a Hypercaloric diet, divided into 5 servings a day, the same one that consists of three main meals plus two snacks. She will take a nutritional control once a month, until the patient is restored, managing to overcome the picture of hepatitis A, along with the degree of obesity present.